2019
DOI: 10.1007/s10533-019-00539-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatially variable bioturbation and physical mixing drive the sedimentary biogeochemical seascape in the Louisiana continental shelf hypoxic zone

Abstract: Seasonal hypoxia on the Louisiana continental shelf (LCS) has grown to over 22,000 km 2 with limited information available on how low oxygen effects the benthos. Benthic macrofaunal colonization and sediment biogeochemical parameters were characterized at twelve stations in waters 10-50 m deep along four transects spanning 320 km across the LCS hypoxic zone in the early fall of 2010 when bottom waters typically return to oxic conditions. Chemical data and sediment profile imaging (SPI) support three primary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…At these stations located on the fringes of hypoxia (Rabalais and Baustian, 2020), they showed that bioturbation recovered rapidly in September, after an oxygen intrusion event in the bottom waters. A similar observation was made by Devereux et al (2019) in late September, with oxic waters and active bioturbation in the sediment of seasonally hypoxic zones. Baustian and Rabalais (2009) and Rabalais and Baustian (2020) indicated that sediments in area of the northern GoM severely impacted by seasonal hypoxia contain smaller, less diverse infauna with lower biomass that are primarily opportunists and either surface deposit feeders or subsurface deposit feeders in the upper centimeter of the sediments, where the organic matter is deposited.…”
Section: Proposed Mechanism: Dysfunction Of Bioturbation During Hypoxsupporting
confidence: 82%
See 2 more Smart Citations
“…At these stations located on the fringes of hypoxia (Rabalais and Baustian, 2020), they showed that bioturbation recovered rapidly in September, after an oxygen intrusion event in the bottom waters. A similar observation was made by Devereux et al (2019) in late September, with oxic waters and active bioturbation in the sediment of seasonally hypoxic zones. Baustian and Rabalais (2009) and Rabalais and Baustian (2020) indicated that sediments in area of the northern GoM severely impacted by seasonal hypoxia contain smaller, less diverse infauna with lower biomass that are primarily opportunists and either surface deposit feeders or subsurface deposit feeders in the upper centimeter of the sediments, where the organic matter is deposited.…”
Section: Proposed Mechanism: Dysfunction Of Bioturbation During Hypoxsupporting
confidence: 82%
“…Numerous publications have described the life conditions of demersal and benthic fauna in the context of hypoxia (Rabalais et al, 2001a(Rabalais et al, ,b, 2002Levin et al, 2009;Middelburg and Levin, 2009;Briggs et al, 2015;Devereux et al, 2019;Rabalais and Baustian, 2020). Hypoxic areas are known as "Dead Zones" due to the scarcity of fishable species that leave the area when oxygen is below the hypoxic threshold of 63 µmol L −1 (Rabalais et al, 2001b).…”
Section: Proposed Mechanism: Dysfunction Of Bioturbation During Hypoxmentioning
confidence: 99%
See 1 more Smart Citation
“…Using δ 30 Si signals, we infer two pathways for formation of acid‐leachable reactive silica and suggest LSi (with some refractory bSiO 2 ) requires fewer and less exaggerated fractionation steps than bSiO 2 , although bSiO 2 δ 30 Si is well correlated to that of the acid‐leachable pool. Furthermore, we have shown independently (without aid of electron microscopy) that a majority of the water‐column diatom bSiO 2 in these sediments is altered rapidly (on the order of months) during early diagenesis in the surface sediments, as sediment deposition in the Mississippi delta can be variable (upward of 10 cm a −1 ) (Adhikari et al, 2016; Chen et al, 2005; Devereux et al, 2019). Given eutrophication in the river waters feeding this system, which have led to increasing bSiO 2 in regional sediments, the strength of this process as an elemental sink may have increased in the last half century.…”
Section: Discussionmentioning
confidence: 98%
“…Remineralization rates of organic matter due to denitrification are often less than rates of manganese‐ and iron‐oxides reduction. The latter two processes are the dominant anaerobic processes in the upper 10 cm of sediment cores across the nGoM shelf (Devereux et al, 2015, 2019). Manganese‐ and iron‐oxides reduction and sulfate reduction all increase TA at a faster rate than DIC (Cai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%